2017
DOI: 10.1590/s0102-865020170110000008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atenolol pre-treatment in heart damage in a model of intestinal ischemia-reperfusion

Abstract: 1 AbstractPurpose: To investigate the effects of atenolol in inflammatory mediator and oxidative stress in a myocardial injury by intestinal ischemia/reperfusion in rat model. Methods: Adult Wistar male rats were randomly (n=8), anesthetized and divided in: Sham: submitted to operation only; group SS+IR: intravenous saline infusion following superior mesenteric artery occlusion during 60 minutes (ischemia) and open for 120 minutes (reperfusion); group AT+IR: intravenous atenolol infusion (2 mg/kg) following su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Okada et al [45] demonstrated through an animal model of intestinal ischemia and reperfusion (IRI) that there is a direct relationship between increases in malondialdehyde (MDA), reactive oxygen species (ROS) and TNF-alpha and cardiac injuries, as the study demonstrated that the MDA content and TNF-alpha quantified from hearts obtained from animals belonging to the Sham group (shamoperated) was statistically lower when compared with hearts from animals in the control group, that is, animals treated with 0.9% saline solution and subjected to IRI. These results corroborate that the antioxidant and anti-inflammatory effects of EPI may be responsible for the decrease in AVB and LET in animals treated with EPI and subsequently subjected to the CIR protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Okada et al [45] demonstrated through an animal model of intestinal ischemia and reperfusion (IRI) that there is a direct relationship between increases in malondialdehyde (MDA), reactive oxygen species (ROS) and TNF-alpha and cardiac injuries, as the study demonstrated that the MDA content and TNF-alpha quantified from hearts obtained from animals belonging to the Sham group (shamoperated) was statistically lower when compared with hearts from animals in the control group, that is, animals treated with 0.9% saline solution and subjected to IRI. These results corroborate that the antioxidant and anti-inflammatory effects of EPI may be responsible for the decrease in AVB and LET in animals treated with EPI and subsequently subjected to the CIR protocol.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] used this classification to show the efficiency of diltiazem plus SOD on IRI [ 12 ] . In another study, Okada et al investigated the protective effect of atenolol on myocardial cells in regard to the histopathological classification abovementioned [ 13 ] . In the present study, we found significantly less histopathological damage in Wistar rats’ myocytes when cilostazol was used ( Figures 1 and 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The bowel is sensitive to ischemia because of its high metabolic activity 19 ; resulting in worsening of wound healing after anastomoses 5.7 , increased fistulas tax, and difficulty in adequate nutrients’ absorption, causing malnutrition, anemia and diarrhea. It is one of the main sources of bacteria causing sepsis, which happens with the breakdown of the intestinal barrier allowing wide bacterial translocation 17 .…”
Section: Introductionmentioning
confidence: 99%